Bacteria of the genus Pseudomonas isolated from Antarctic substrates - S. Hnatush; S. Komplikevych; O. Maslovska; O. Moroz; T. Peretyatko; A. Dzhulai; T. Krasnozhon (Ukrainian Antarctic Journal, 2021)
The study’s primary purposes were establishing the number of microorganisms that exhibit hydrolytic activity in Antarctic soil and mosses samples, isolation of metal-resistant strains of bacteria, and description of their physiological and biochemical properties. Samples collected during the XXIII Ukrainian Antarctic Expedition in 2019 were used. The number of colony-forming units of microorganisms exhibiting proteolytic, amylolytic, cellulase, lipolytic activity was studied. Pure bacterial cultures were isolated using standard microbiological methods. Determination of resistance of isolates to heavy metals was estimated after their cultivation during ten days on agar plates with different concentrations of CdCl2 ⋅ 2.5H2O, CoCl2 ⋅ 6H2O, K2Cr2O7, FeSO4 ⋅ 7H2O, CuCl2 ⋅ 2H2O. Identification of strains was based on the sequencing of the 16S rRNA gene, morphological, physiological, and biochemical properties. Among the 23 isolates, nine metal-resistant strains were selected, four of which were identified as Pseudomonas yamanorum ІМV B-7916 and 79_102, and as P. arsenicoxidans 5A_1N_24, and 89_1T_89. Among the selected strains, the most resistant to heavy metals was P. yamanorum 79_102. All studied strains synthesize lipases during growth on medium with tween-20, which contains 0.5–1 mM of ferrous sulfate and copper (II) chloride. The studied strains produce exopolysaccharides during growth at 6 and 22 °C. The most effective among these strains exopolysaccharides are synthesized by P. arsenicoxidans 5A_1N_24 — 768 mg/g of dry weight. Our results expand the knowledge about the diversity of microorganisms of extreme biotopes, their properties, resistance to heavy metal compounds.